The Role of Media in Supporting National Security: (Press the Name of the Time of the Month of Kurdistan, Which Has a Length of Time) - Shareef, Hawkar Y.; Ahmad Sapan, Magedad Kh. (Mitanni Journal of Humanitarian Sciences, 2023)
The purpose of this research is to identify the most significant frameworks and motives implemented by Kurdish institutions to enhance national security. It used research and survey method and relied on analyzing the agency’s content to reach the Kurds. The research group, which includes the newspaper "Khafat" as an example of the research, includes 14 speeches of President Massoud Barzani, President of Kurdistan, and 20 speeches given by politicians, literature, and cultures during the days of the month-long campaign. And one of the most significant results of this research is that the articles published during this period were more supportive of the framework of national responsibility and security.